INDIAN LANGUAGES IN ELECTION MANIFESTO OF SEVENTEENTH LOK SABHA ELECTION-2019 IN THE INTEREST OF STRENGTHENING DEMOCRACY: लोकतंत्र की मज़बूती के हित में सत्रहवीं लोकसभा चुनाव -2019 के चुनावी घोषणा-पत्रों में भारतीय भाषाएँ - Sharma, Anuradha (International Journal of Research -GRANTHAALAYAH, 2019)
Democracy is a system that respects the feelings of the people. But some experience in the context of India is the opposite. Here in the name of democracy, the system, which removes the system from the language of 'Lok', has continued to dominate. In this vision, words are called out, calling it true and good democracy. Distance from the local language of administration is the root of many problems, so the insistence on keeping distance from the language of justice puts a question mark on justice. The side effect of this is that education is also embracing the language which negates the self-respect of the folk language. The most negative aspect of Indian democracy is to alienate Indian languages ​​from their natural rights. लोकतंत्र लोक की भावनाओं का आदर करने वाली व्यवस्था है। लेकिन भारत के संदर्भ में कुछ अनुभव इसके विपरीत है। यहां लोकतंत्र के नाम पर व्यवस्था को ‘लोक’ की भाषा से दूर करने वाले ‘तंत्र’ लगातार हावी रहे हैं। इस दृष्टि में उसे सच्चा और अच्छा लोकतंत्र कहते हुए शब्द ठिठकते है। प्रशासन की लोक भाषा से दूरी अनेक समस्याओं का मूल है तो न्याय की लोक की भाषा से दूरी बनाये रखने की जिद्द न्याय पर प्रश्नचिन्ह लगाती है। इसी का दुष्प्रभाव है कि शिक्षा भी उस भाषा से आलिंगन कर रही है जो लोक भाषा के स्वाभिमान को नकारती है। भारतीय भाषाओं को उनके स्वाभाविक अधिकारों से विमुख करना भारतीय लोकतंत्र का सर्वाधिक नकारात्मक पक्ष है।